RE-IMAGINING BLACK SCIENTIST IN HIDDEN FIGURES (2016) - Rini Uswatun Hasanah; Much Koiri (Universitas Negeri Surabaya, 2022)
Hidden Figures clearly show how the injustice committed by white people against black people as a society with majority status treat black people in Virginia, United States. This study aimed to represent Black Scientist characters and the intersectionality of racialized, gendered, and classed identity in reconceptualization of Black Feminism by Patricia Hill Collins. As can be seen in Hidden Figures, Theodore Melfi’s illustrated the lives of the Black Scientists to prove that they could achieve success. The research in Hidden Figures points out that Black scientists experienced sexism, racism, and classism as intersecting oppression. The state of being subjected to tyranny. The experience of facing gender, race, and socioeconomic discrimination in everyday life. Black Scientist women respond to prejudice by succeeding in their jobs via hard effort, exploiting the system and working against it, disregarding the prejudice, concentrating on their good fortune, and urging others to join the struggle. It becomes clear that the Black Scientist characters also have the qualities and thoughts of Black Feminists, which lead to conflicting behaviours. Finally, the characters' re-imagining of Black Feminist leads to the establishment of Black Scientist orientation and empowerment, which results in the characters' lives.